Eksistensi Semu sebagai Fenomena Syndrom Hiperrealitas - Nurhaeni (STAI DDI Kota Makassar, 2021)
Existence in social space is not really real, but each has its strength. It is not only the positive benefits one can derive through this existence, but also the negative dangers which have a profound effect on one's character. The pseudo-existence must be used wisely by those who bear it so that it does not violate the rules for using internet media. The desire for a social community as a primary need as a social being is a phenomenon that occurs because of a syndrome, where the syndrome is known as hyperreality syndrome. When someone uploads a photo of himself, a few moments later the same thing will be done by other users. However, not all of what is emblazoned in the feed or the new media homepage is of positive value.